ESSENTIAL OIL AND CARVACROL CONTENT OF OREGANO (ORIGANUM SPP.) SPECIES GROWN IN WILD AND CULTIVATED CONDITIONS OF ANTALYA - Turgut, K.; Tugrul Ay, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The objective of this study was to investigate variability of essential oil and carvacrol content of five oregano species (O. saccatum, O. solymicum, O .majorana, O. onites and O. vulgare subsp. hirtum) collected from the natural flora of Antalya, Turkey. Samples were collected from early inflorescences, inflorescences and late inflorescences stages of 5 species grown in wild and cultivated conditions. Essential oils were obtained via steam distillation using Clevenger-type apparatus and they were analyzed with Gas Chromatography (GC). The highest average essential oil rate was obtained from inflorescences stage of wild O. majorana (8.2%) and followed by late inflorescences stage of wild O. majorana (6.1%) and inflorescences stage of cultivated O. onites (5.7%). Although cultivated O. majorana plants revealed lower essential oil rate than wild O. majorana, in the other species cultivated plants gave higher essential oil percentage. Eighteen compounds were identified in the essential oil of oregano species under studied conditions. The highest rate of carvacrol was found at the early inflorescences stage of cultivated O. majorana (53.90%) and followed by inflorescences stage of wild O. majorana (52.40%) and early inflorescences stage of wild O. majorana (50.10%). In general, rate of carvacrol in the wild and cultivated O. majorana, O. solymicum, O. onites and O. vulgare subsp. hirtum plants were appeared to be quite similar. However, percentage of carvacrol was found to be higher in the cultivated O. saccatum plants (average 40%) than wild O. saccatum plants (average 30%). Acknowledgements: Funded by Akdeniz University Scientific Research Project Unit